Influence of five soybean cultivars on the consumption, development and fertility of Anticarsia gemmatalis - Marques, Gabriela E. Lesche; Corseuil, Elio Corseuil (Pesquisa Agropecuaria Brasileira, 2014)
The present work was conducted during 1980/81 at the Centro Nacional de Pesquisa de Trigo of EMBRAPA, located in Passo Fundo, RS, Brazil, under laboratory conditions with a temperature of 29 ± 2.5°C, photoperiod of 14 hours, and moisture of 70 ± 10% its objective was to evaluate the effect of soybean (Glycine max (L.) Merrill) cultivars Paraná, Cobb, BR 1, BR 3 and BR 4 during the late vegetative stage of plants, on the leaf consumption, development, fecundity and fertility of Anticarsia gemmatalis Hübner (1818). The influence of sex on the leaf consumption, and on the total duration of immature stages was verified. Significant effects of cultivars were observed on leaf consumption, efficiency of ingested food conversion by the caterpillars, duration of imature stages, fertility rate, and biotic potential. The greatest resistance of 'Cobb’ and lower resistance of BR 3' and BR 4' was evidenced.